2007
DOI: 10.1016/j.gca.2007.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of calcite growth rate and Sr partitioning on solution stoichiometry: Non-Kossel crystal growth

Abstract: Seeded calcite growth experiments were conducted at fixed pH (10.2) and two degrees of supersaturation (X = 5, 16), while varying the Ca 2+ to CO 3 2À solution ratio over several orders of magnitude. The calcite growth rate and the incorporation of Sr in the growing crystals strongly depended on the solution stoichiometry. At a constant degree of supersaturation, the growth rate was highest when the solution concentration ratio, r = [Ca 2+ ]/[CO 3 2À ], equaled one, and decreased symmetrically with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
198
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(221 citation statements)
references
References 44 publications
21
198
2
Order By: Relevance
“…4B), an increase of 0.008 mmol/mol of Sr/Ca per salinity unit is observed. According to Lorens (1981), Nehrke et al (2007) and Tang et al (2008), higher calcite Sr/Ca ratios are mainly associated with higher growth rates in inorganic calcite which is also observed in biogenic calcite (Kısakürek et al, 2008). Results from inorganic experiments (Zuddas and Mucci, 1998) furthermore indicate a positive linear correlation between calcite precipitation rate and ionic strength of the solution.…”
Section: Effect Of Salinity On Mg/ca and Sr/ca Ratiosmentioning
confidence: 81%
See 2 more Smart Citations
“…4B), an increase of 0.008 mmol/mol of Sr/Ca per salinity unit is observed. According to Lorens (1981), Nehrke et al (2007) and Tang et al (2008), higher calcite Sr/Ca ratios are mainly associated with higher growth rates in inorganic calcite which is also observed in biogenic calcite (Kısakürek et al, 2008). Results from inorganic experiments (Zuddas and Mucci, 1998) furthermore indicate a positive linear correlation between calcite precipitation rate and ionic strength of the solution.…”
Section: Effect Of Salinity On Mg/ca and Sr/ca Ratiosmentioning
confidence: 81%
“…We also observe that the regression model predicts a statistically significant Sr/Ca variability due to changes in Ω (p b 0.001; Table 3). In inorganic and biogenic calcite, the Sr/Ca ratio is known to increase with growth rate (Lorens, 1981;Nehrke et al, 2007;Tang et al, 2008;Kısakürek et al, 2008), and a higher [CO 3…”
Section: Effect Of Calcium Carbonate Saturation State (ω) On Mg/ca Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The likeliest explanation for most of the discrepancy is that the surface of the calcite spar used in this study has a much lower reactive site density than the calcite seed used in the other studies. A study of calcite precipitation on Iceland spar conducted by Nehrke et al [2007] made use of calcite that was essentially identical to that used in the experiments in this study. Nehrke et al [2007] reported rates ranging from about 10 -6 to 10 -7 mol•m -2 •s -1 , or still 1-2 orders of magnitude faster than those reported here.…”
Section: Interpretation Of Rates From Stirred Reactorsmentioning
confidence: 99%
“…A study of calcite precipitation on Iceland spar conducted by Nehrke et al [2007] made use of calcite that was essentially identical to that used in the experiments in this study. Nehrke et al [2007] reported rates ranging from about 10 -6 to 10 -7 mol•m -2 •s -1 , or still 1-2 orders of magnitude faster than those reported here. However, their surface area normalization was based on grain geometry rather than a BET measurement, with the result that their reported specific surface area was about 1-2 orders of magnitude lower than that determined here.…”
Section: Interpretation Of Rates From Stirred Reactorsmentioning
confidence: 99%